PEMBELAJARAN SASTRA SEBAGAI SARANA PENGEMBANGAN KARAKTER DAN LITERASI DI SEKOLAH MENENGAH PERTAMA (SMP) - Sitepu, Ayu Wandira br; Sitinjak, Yolanda Vera Nicole; Harahap, Safinatul Hasanah (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
Literature education in junior high schools plays an important role in shaping students' character and improving their literacy skills. However, in practice, literature education often focuses on cognitive aspects and text structure analysis, so that the moral and humanitarian values contained in literary works are not fully explored. This study aims to examine how literature education can be an effective means of developing the character and literacy of junior high school students through a literature study approach. The method used is a literature review based on the results of research from national and international journals over the last five to ten years (2018–2024). The results of the study show that literature learning that integrates character values and literacy activities can increase students' empathy, responsibility, and creativity. A contextual, participatory, and local literature-based learning approach has proven to be more effective in fostering reading interest and strengthening students' cultural identity. Thus, literature learning is not only a means of language and aesthetic appreciation, but also a medium for character education that is relevant to the needs of 21st-century education. ABSTRAKPembelajaran sastra di Sekolah Menengah Pertama (SMP) memiliki peran penting dalam membentuk karakter dan meningkatkan kemampuan literasi siswa. Namun, dalam praktiknya, pembelajaran sastra sering kali masih berfokus pada aspek kognitif dan analisis struktur teks, sehingga nilai-nilai moral dan kemanusiaan yang terkandung di dalam karya sastra kurang tergali. Penelitian ini bertujuan untuk mengkaji bagaimana pembelajaran sastra dapat menjadi sarana efektif dalam pengembangan karakter dan literasi siswa SMP melalui pendekatan kajian literatur. Metode yang digunakan adalah kajian pustaka berdasarkan hasil penelitian dari jurnal-jurnal nasional dan internasional selama lima hingga sepuluh tahun terakhir (2018–2024). Hasil kajian menunjukkan bahwa pembelajaran sastra yang mengintegrasikan nilai-nilai karakter serta kegiatan literasi mampu meningkatkan empati, tanggung jawab, dan kreativitas siswa. Pendekatan pembelajaran yang kontekstual, partisipatif, dan berbasis karya sastra lokal terbukti lebih efektif dalam menumbuhkan minat baca serta memperkuat identitas budaya siswa. Dengan demikian, pembelajaran sastra bukan hanya menjadi sarana apresiasi bahasa dan estetika, tetapi juga media pendidikan karakter yang relevan dengan kebutuhan pendidikan abad ke-21.